SPEECH ETIQUETTE IN COMMUNICATIVE SITUATIONS AND STRUCTURAL ANALYSIS OF LINGUISTIC UNITS: A COMPARATIVE STUDY OF ENGLISH AND UZBEK LANGUAGES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This scientific article aims to explore the speech etiquette observed in communicative situations and the structural analysis of linguistic units in English and Uzbek languages. The study focuses on the similarities and differences in speech etiquette practices and the structural components of language in these two languages. The analysis is based on a comprehensive review of existing literature and references from reputable sources. The findings provide valuable insights into the cultural and linguistic aspects of communication in English and Uzbek languages.